The α‐melanocyte‐stimulating hormone/melanocortin‐1 receptor interaction: A driver of pleiotropic effects beyond pigmentation. (2nd May 2021) - Herraiz, Cecilia; Martínez‐Vicente, Idoya; Maresca, Vittoria
Abstract: Melanocortin‐1 Receptor (MC1R), when stimulated by alpha‐melanocyte‐stimulating hormone (α‐MSH), is a driver of eumelanogenesis. Brown/black eumelanin is an effective filter against ultraviolet radiation (UVR) and is a scavenger of free radicals. Several polymorphic variants of MC1R are frequent in red‐head people. These polymorphisms reduce the ability of MC1R to promote eumelanogenesis after its activation and spontaneous pheomelanogenesis take place. Since pheomelanin can act as an endogenous photosensitizer, people carrying MC1R polymorphisms are more susceptible to skin cancer. Here, we summarize current knowledge on the biology of MC1R beyond its ability to drive eumelanogenesis. We analyze its capacity to cope with oxidative insult and consequent DNA damage. We describe its ability to transduce through different pathways. We start from the canonical pathway, the cAMP/protein kinase A (PKA) pathway mainly involved in promoting eumelanogenesis, and protection from oxidative damage, and we then move on to describe more recent knowledge concerning ERK pathways, phosphoinositide 3‐kinase (PI3K) pathway/AKT, and α‐MSH/Peroxisome proliferators activated receptor‐γ (PPAR‐γ) connection. We describe MC1R polymorphic variants associated with melanoma risk which represent an open window of clinical relevance.